Fish Mortalities Linked to Harmful Algal Bloom of Cochlodinium polykrikoides in Lampung Bay - Endang Sunarwati Srimariana; Meutia Samira Ismet; H.A.W Cappenberg; Tumpak Sidabutar (Contemporary Research and Perspectives in Biological Science Vol. 3, 2024)
In October and November 2012, the waters of Lampung Bay in Indonesia turned dark reddish-brown due to a harmful algal bloom (HAB) caused by a rapid increase in phytoplankton, commonly known as red tide. This event resulted in the mass death of fish farmed in floating nets. The bloom was driven by the dinoflagellate Cochlodinium polykrikoides, the first documented occurrence of this species in Indonesian waters, with peak concentrations of 3.07 x 107 cells L-¹. Since this event, similar blooms have occurred in the following years, though they have not always resulted in significant fish mortality. Water samples for nutrient analysis were collected using a 20 \(μ\)m mesh plankton net and Nansen bottles at a depth of one meter, focusing on nitrate and phosphate levels. The results suggest that fish kills were primarily due to nighttime hypoxia, likely caused by phytoplankton blocking the fish’s gills. The bloom onset was associated with a high nitrate-to-phosphate ratio, suggesting that nitrate acted as the main trigger while phosphate was the limiting factor for flower development. This study represents the first documented bloom of Cochlodinium polykrikoides in Lampung Bay and highlights the critical role of nutrient imbalances in the occurrence of harmful algal blooms and their significant ecological impacts on coastal ecosystems in Indonesia.